Intellectual Capital and Financial Performance in an Emerging Economy: An Empirical Investigation of a Nigerian Bank - Ekwe, Michael Chidiebere (Ushus Journal of Business Management, 2012)
The general belief that employees of an organization are important assets to that organization has not been empirically proved as not many studies have investigated the relationship or association between the intellectual capital components and the organizational performance indices.